7,8-Dihydroxyflavone and Neuropsychiatric Disorders: A Translational Perspective from the Mechanism to Drug Development - Yang, Shaojie; Zhu, Guoqi (Current Neuropharmacology, 2022)
7,8-Dihydroxyflavone (7,8-DHF) is a kind of natural flavonoid with the potential to cross the blood-brain barrier. 7,8-DHF effectively mimics the effect of brain-derived neurotrophic factor (BDNF) in the brain to selectively activate tyrosine kinase receptor B (TrkB) and downstream signaling pathways, thus playing a neuroprotective role. The preclinical effects of 7,8-DHF have been widely investigated in neuropsychiatric disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), depression, and memory impairment. Besides the effect on TrkB, 7,8-DHF could also function through fighting against oxidative stress, cooperating with estrogen receptors, or regulating intestinal flora. This review focuses on the recent experimental studies on depression, neurodegenerative diseases, and learning and memory functions. Additionally, the structural modification and preparation of 7,8-DHF were also concluded and proposed, hoping to provide a reference for the follow-up research and clinical drug development of 7,8-DHF in the field of neuropsychiatric disorders.
Keywords: learning and memory